2003
DOI: 10.1080/07924259.2003.9652529
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of spermiogenesis and spermatozoa ofNotocotylus neyraiGonzález Castro, 1945 (Digenea, Notocotylidae), intestinal parasite ofMicrotus agrestis(Rodentia: Arvicolidae) in Spain

Abstract: To our knowledge, this is the first ultrastructural study on spermiogenesis and the spermatozoon of a trematode belonging to the family Notocotylidae, Notocotylus neyrai. Spermiogenesis begins with the formation of the zone of differentiation which comprises striated rootlets associated with the two centrioles and an intercentriolar body in-between. It is characterised by an asynchronic flagellar rotation and subsequent proximodistal fusion with a median cytoplasmic process. The migration of the nucleus toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
68
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 24 publications
(34 reference statements)
2
68
0
Order By: Relevance
“…In D. hospes, at least one of the two free flagella grows externally to the median cytoplasmic process with an angle of about 120°. This fact has also been observed in other digeneans such as F. hepatica (Ndiaye et al 2003a), H. fasciata (Levron et al 2003) and M. parvus . Moreover concerning the latter species, Levron et al (2004) describe an angle of 120°for both free flagella.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In D. hospes, at least one of the two free flagella grows externally to the median cytoplasmic process with an angle of about 120°. This fact has also been observed in other digeneans such as F. hepatica (Ndiaye et al 2003a), H. fasciata (Levron et al 2003) and M. parvus . Moreover concerning the latter species, Levron et al (2004) describe an angle of 120°for both free flagella.…”
Section: Discussionmentioning
confidence: 56%
“…Spermiogenesis Spermiogenesis in D. hospes follows the general pattern described for other digenean species (Mohandas 1983;Orido 1988;Stitt and Fairweather 1990;Gracenea et al 1997;Miquel et al 2000;Baptista-Farias et al 2001;Ndiaye et al 2003a). The presence of two centrioles and striated rootlets and also a proximodistal fusion are general characteristics of parasitic Platyhelminthes Ase anterior spermatozoon extremity, Ax axoneme, Ce cytoplasmic expansion, Cm cortical microtubules, D doublets, Eo extramembranar ornamentation, G granules of glycogen, Mt (number) mitochondria, N nucleus, n several, Pse posterior spermatozoon extremity, Sb spine like bodies.…”
Section: Discussionmentioning
confidence: 89%
“…This fusion zone is marked by the presence of four electron dense lines, which appear during the spermiogenesis and persist in the mature spermatozoon. This phenomenon has also been described in many other digenean species: one Haematoloechidae, Haematoloechus medioplexus (Burton 1972), one Didymozoidae, Gonapodasmius (Justine and Mattei 1982a), one Dicrocoeliidae, Corrigia vitta (Robinson and Halton 1982), two Microphallidae, Maritrema linguilla (Hendow and James 1988) and Microphallus primas (Castilho and Barandela 1990), one Haploporidae, Saccocoeliodes godoyi , three Opecoelidae, Opecoeloides furcatus (Miquel et al 2000), Helicometra fasciata (Levron et al 2003), Monorchis parvus (Levron et al 2004a), one Brachylaimidae, Scaphiostomum palaearcticum (Ndiaye et al 2002), one Notocotylidae, Notocotylus neyrai (Ndiaye et al 2003b), two Fasciolidae, Fasciola hepatica (Ndiaye et al 2003a) and Fasciola gigantica (Ndiaye et al 2004), one Paramphistomidae, Paramphistomum microbothrium (Seck et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Such spinelike bodies were described for the first time by Miquel et al (2000) in Opecoeloides furcatus (Opecoelidae). Other recent studies have shown the existence of spinelike bodies in Notocotylus neyrai (Ndiaye et al 2003b), Poracanthium furcatum (Levron et al 2004b), Fasciola gigantica (Ndiaye et al 2004), Dicrocoelium hospes (Agostini et al 2005), Troglotrema acutum (Miquel et al 2006), Crepidostomum metoecus (Quilichini et al 2007a), Nicolla wisniewskii (Quilichini et al 2007b), N. testiobliquum (Quilichini et al 2007c) and Paramphistomum microbothrium (Seck et al 2007). But in these species, except for the last one, the spinelike bodies are not located on the lateral expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation